(untitled) (Journal of the College of Basic Education, 2022)
The current research dealt with the study of the traits of talented students in the Department of Art Education according to the age variable through expressive and aesthetic artwork, as the traits of gifted students according to the gender variable is what we are looking for in the drawings of talented students in an effort to clarify those features that characterize the talented students in the Department of Art Education. The researchers used the descriptive approach to define the concept of gifted in the field of art education, and this was done after reviewing a large group of definitions that differed according to the different factors associated with them, then the researcher classified these definitions based on the factors associated with them into: talent, intelligence, creativity, acumen, excellence Genius, excellence, foresight. Thus, the descriptive research method was adopted, as it is the most appropriate method to achieve the goal of the research. The research included a community of (400) students, and a random sample of (200) students was selected. The research tool was designed based on the indicators of the theoretical framework and previous studies. He extracted honesty and consistency and concluded the chapter with the most important results, conclusions, recommendations and suggestions